Validação dos limites de quantificação para análise das contagens padrão em placas e de células somáticas no leite por citometria de fluxo - Rosemary dos Santos Conrrado (2023)
In recent decades, advances in technology and production have required the development o accurate and reliable analytical methods. In order to compare and verify the reliability of these methods, regulatory agencies and institutions determine and regulate standards that allow their validation, certifying as required methodological parameters. In Brazil, INMETRO is the regulatory agency which validates analytical methodologies, through the document DOQ-CGCRE-008, as well as the standards related to each analyte. Flow cytometry is an analytical methodology used quantification of microbial standard plate count (SPC) and somatic cell count (SCC) in raw milk samples. In Brazil, this methodology is referenced by the Ministry of Agriculture (MAPA), as the one to be followed by the laboratories of the Brazilian Network of Milk Quality Control Laboratories (RBQL) for analysis of SCC and SPC, in compliance with Instruction Normative 77 of 2018/MAPA. The aim of the present study was to validate the limits of quantification of SPC and SCC using the flow cytometry methodology, following the guidance document DOQ-CGCRE-008, as well as the rules related to each analyte. The analytical parameters used for validation (linearity, accuracy, precision and uncertainty) were evaluated before determining the limits of quantification. Accuracy was confirmed by methods comparison, where a positive correlation was observed between methods, also assessed by calibration using certified reference material and by studying the proficiency test through the evaluation of the Z score. Accuracy was confirmed by repeatability and reproducibility. Measurement uncertainty was assessed on the somatic cell count analytic. Accuracy was confirmed by repeatability and reproducibility. Uncertainty was measured for the somatic cell count. After analyses, it was observed that the statistical data were within the limits established by the norms and consistent with those found in the literature. The present study determined as quantification limit: 1 UFC x 1000/mL for SPC and 1 cell x 1000/mL for SCC. This work highlights the importance of method validation, which enables knowledge of the limitations and reliability of the measurements, such as the quantification limits.